Considerations on Cultural Studies in Brazil - Wortmann, Maria Lúcia Castagna (2019)
From a review of articulations between Cultural Studies and theories of social communication, anthropology, social sciences, literary theory and education in Brazil, the academic production of concepts, perspectives and approaches in research is highlighted. The study involved: (a) a comprehensive search on the major international journals of Cultural Studies; (b) a search on Google Scholar and other specific platforms; (c) an analysis of institutional affiliations, research groups, résumés on Lattes platform, and interviews available online. At the end, this study presents political-academic considerations about studies conducted in Brazil in articulations with Latin American Cultural Studies.